Comprensión lectora en el desarrollo de habilidades cognitivas en el cuarto año de educación básica durante el periodo 2019 - Murillo Henriquez, Erika del Rocio (2019)
The following research aims to identify and identify the main difficulties. Development of an experiment conducted with students in the fourth year of basic education, as part of a research project entitled Reading Comprehension in the Development of Cognitive Skills in the fourth year of basic education during the 2019 period, because it is a feasible project. It consists of a diagnosis of the situation and the design and implementation of a proposal, to contribute to the situation of the problems detected. Reading is a process by which people acquire new knowledge, practice it and learn to raise awareness, it is a very precious value not only for them as human beings but for the entire society that surrounds them. The information gathering technique was; direct observation and questions based on questionnaires, and as an instrument, the 25 students of the fourth year of basic education, the results of the application of the proposal revealed the importance of the active participation of students in reading activities for reading comprehension; For example, by selecting the text to read, they demonstrated the effectiveness of previous knowledge about the implementation of the reader's cognitive strategies. There are different reading techniques that every reader must know to master to have better skills as such, the different techniques develop the skills which is the primary objective, it will help the reader to make the text lighter and less tedious.